Survival and complications of unconventional fixed dental prosthesis for maintaining diastema and splint pathologically migrated teeth: A case series up to 8 years follow-up - Sudhir Bhandari; Sonika Bakshi (Wolters Kluwer Medknow Publications, 2013)
Spacing in dentition negatively interferes with harmony of the smile. A lot of literature has been devoted to prosthetic closure of such space(s) in the dentition; however, the only option for maintaining space(s) in tooth-supported fixed dental prosthesis (FDP) is with the aid of loop connectors. Eleven patients (seven males and four females) with mean age of 45.18 years (range 22-70 years), previously treated with porcelain fused to metal full coverage restorations joined with loop connectors, were evaluated clinically to assess the clinical status and longevity of treatment provided. All the patients were asked to fill a simple close-ended questionnaire to provide their perspective on the limitations and outcome of the treatment and rate their satisfaction level on the scale of 1-10. The cumulative survival of the FDPs with the aid of loop connectors was 90.9%. There was no reported esthetic failure and, at the time of responding to the questionnaire, none of the patients had active complaint with respect to the prosthesis and all but one of the patients were satisfied with the treatment provided. Clinical survivability and the patient feedback suggests that customized designing of loop connectors for each patient is an excellent treatment modality to successfully maintain excessive (single/generalized) spacing between teeth and effectively splint pathologically migrated and mobile teeth. The reported problems with this treatment option are all transient in nature.